2005
DOI: 10.1293/tox.18.69
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for DNA-Reactive (Genotoxic) Organic Carcinogens

Abstract: This paper reviews the evidence for thresholds for DNA-reactive carcinogens and presents dose response data for effects in rat liver of two DNA-reactive hepatocarcinogens, diethylnitrosamine and 2-acetylaminofluorene, which is consistent with thresholds. (J Toxicol Pathol 2005; 18: 69-77)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…40,41 Several factors could account for a NOAEL for adducts. Accordingly we suggest that this low level CD is a threshold for DNA adduct formation and hence carcinogenicity, as previously discussed.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Several factors could account for a NOAEL for adducts. Accordingly we suggest that this low level CD is a threshold for DNA adduct formation and hence carcinogenicity, as previously discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of these effects and the extent to which they interact with background effects is difficult, though a quantitative estimate has been made by Williams et al 49 Considering that the spontaneous DNA modifications of a mammalian cell is about one lesion per 10 6 bases, the lowest DNA adduct levels of three genotoxic carcinogens was determined to be one adduct per 10 8 nucleotides, which is far below the spontaneous DNA modifications and considered unlikely to be of biological significance.…”
Section: Discussionmentioning
confidence: 99%
“…15 Beyond considering species and individual differences in the capacity of metabolic activation and inactivation several aspects in DNA binding, DNA repair and mutations are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The LNT model predicted that a single alteration of DNA could initiate the process of carcinogenesis, and that once initiated, this process was irreversible. However, this assumption has been consistently shown to be false (77). In one such study Driver et al (78) demonstrated that a single administration of the mutagen/carcinogen dimethylnitrosamine (DMN) induced a linear dose response for renal mesenchymal DNA adducts (early cancer process stage), as well as for mesenchymal foci (later cancer process stage), observations consistent with the LNT model.…”
Section: Mechanistic Challenges To Lnt-hit Modelmentioning
confidence: 93%